African American male students in preK-12 schools : informing research, policy, and practice - Moore, James L., III (Advances in race and ethnicity in education, 2014)
African American Males in PreK-12 Schools: Informing Research, Practice, and Policy presents a comprehensive viewpoint on preK-12 schooling for African American males. Including theoretical, conceptual, and research based chapters, this edited volume offers readers compelling evidence of the education challenges and successes for this student population. Each chapter provides a richer perspective of the experiences of African American males throughout their elementary and secondary education. Additionally, each chapter includes strong implications for education research, practice, and policy, as well as concrete recommendations to important stakeholders, such as educators, school counselors, parents, etc. Collectively, the contributors communicate throughout the edited volume that educational change is needed and that educational success is attainable for African American males. It is intended that the edited volume will help inform education research, practice, and policy as they relate to African American males. Equally important, it is envisioned that the readers will develop a greater interest in the education of African American males.